An assessment of the role played by Polokwane Local Municipality in service delivery within Manthorwane Community of Limpopo Province - Mmola, Dinkgolang Matildah (University of Limpopo (Turfloop Campus), 2012)
The main purpose of this study was to assess the role played by Polokwane Local Municipality in delivery of basic services such as water, sanitation, electricity , and housing in the village of Manthorwane, Limpopo Province. It was of critical importance for the researcher to investigate this area, as there was no study done before related to basic services delivery. The objectives of the study were ,to assess the extent to which the municipality is providing basic services, investigate the strength, weaknesses , examine the impact of the Municipality‘s role in the development of Manthorwane Village and recommending strategies for enhancing the level of basic service delivery. Qualitative and quantitative research methods were used because the study combines the use of instruments and methods for measurement and the way the researcher interacts with the people. Interviewees and questionnaires were used to understand the community’s feeling towards delivery of basic services. The researcher has gone through a detailed process of investigation, where it is found that there is no delivery of basic services (electricity, sanitation, housing). Only water has been provided in this village. The researcher also discovered that there are no valid reasons why the Polokwane Municipality has not delivered the services above. It is also revealed that there are no stakeholder’s participation and consultations meetings when the decisions for service delivery are taken. Evaluation and monitoring tools are not applied when implementing projects. There are some recommendations proposed to the municipality. The municipality could intensify their training process in a way in which the officials could be productive to the community. Transparency must always be practiced for the municipality to excel in their delivery services. Intergovernmental relationship is also encouraged. Awareness programs must be done effectively so that the community is aware of all activities done in their area.
Thesis (M.DEV.) --University of Limpopo, 2012
Keywords: Basic services; Sanitation; Water; Electricity; Housing; 363.61096827; Community development -- South Africa -- Limpopo Province; Rural electrification; Housing, Rural -- South Africa